Lessons learned from Huizhou, China's unsuccessful waste-to-energy incinerator project: Assessment and policy recommendations. (April 2015) - Wan, Zheng; Chen, Jihong; Craig, Brian
Abstract: The Chinese government has advocated the use of waste-to-energy (WtE) incinerators to manage waste because of their high efficiency, minimal land requirement, and significant impact in terms of reducing solid mass; however, the use of WtE incinerators has been met with strong public resistance. This policy note describes Huizhou's unsuccessful WtE incinerator project. Three specific problems are discussed. First, the use of public-private partnerships to implement such projects has led to lack of transparency and corruption. Second, Huizhou has an inadequate dioxin-control strategy due to less stringent standards than those in the U.S. and Europe, along with poor monitoring practices. Third, China's buffer zone between WtE incinerators and populated areas is just 300 m, even though health impacts can be detected for distances up to 5 km. The case of Huizhou shows that high levels of investment do not necessarily result in advanced operation and management techniques. The lack of openness and transparency in government decision-making and supervision exacerbates the severity of not-in-my-backyard (NIMBY) concerns. A number of policy recommendations follow from this case study. Highlights: The use of waste-to-energy (WtE) incinerators has been met with strong public resistance in China. This policy note describes Huizhou's unsuccessful WtE incinerator project. Public-private partnerships to implement Huizhou project has led to lack of transparency. Lack of a stringent dioxin control strategy is another barrier to WtE incinerator development plans. China's safe distance standard should be reassessed and compensation mechanisms should be employed.